High birefringence, low loss terahertz photonic crystal fibres with zero dispersion at 0.3 THz - 尹国冰 李曙光 王晓琰 刘硕 (Chinese physics B, 2011)
A terahertz photonic crystal fibre （THz-PCF） is designed for terahertz wave propagation. The dispersion prop- erty and model birefringence are studied by employing the finite element method. The simulation result reveals the changing patten of dispersion parameter versus the geometry. The influence of the large frequency band of terahertz on birefringence is also discussed. The design of low loss, high birefringence THz-PCFs with zero dispersion frequency at 0.3 THz is presented.